A Unifying Theory for Quantum Physics, Part 1:: How to Motivate Students to Want to Study Quantum Technologies - Boyd, Jeffrey H. (JOURNAL OF ADVANCES IN MATHEMATICS, 2022)
Is the quantum world as strange as they say? If this were an unsolved mathematics question, we might try a new angle of attack. We know quantum mechanics (QM) is the most accurate and productive science humans ever had, meaning its probability predictions are accurate. Every probability has two square roots. The Born rule says either would produce the same probability. Assume nature uses the negative of QM’s equations. What could that mean? We’d need to revise Feynman’s path-integrals and Schrödinger’s equation. If waves travel in the opposite direction as what QM believes, that could produce the negative equations. No wave-particle duality. Free particles would follow backwards zero-energy waves coming from detectors. This, surprisingly, gets rid of quantum weirdness. Our proposal is that nature uses the negative of QM’s equations because particles follow zero-energy waves backwards. Considerable evidence fits this model, including a neutron-interferometer and the Davisson-Germer experiments, a quantum-eraser experiment, Wheeler-gedanken and double-slit experiments, Bell-test experiments, Stern-Gerlach, and high-energy scattering experiments. Finally, we propose a plan for how to motivate students to want to study quantum technologies, thereby addressing the most prominent problem in QM today: the shortage of an educated workforce, the scarcity of aspiring students.